СОҒЛОМ АВЛОД ТАРБИЯСИДА ЖИСМОНИЙ ТАРБИЯНИНГ ЎРНИ ВА ЖИСМОНИЙ ТАРБИЯ ДАРСЛАРИГА ҚЎЙИЛАДИГАН ПЕДАГОГИК ТАЛАБЛАР - Мырзамбетов, П.Ш. (SCIENCE and SOCIETY, 2021)
This article mentions the pedagogical requirements for the role and importance of physical education in the education of a healthy generation, and its content includes ideas about the principles, methods and tools used in organizing trainings.